Clinic-eeg correlation somatogenous of conditioned febrile seizures in children - Gaffarova V.F (Research Parks Publishers, 2021)
The article describes the outcomes of febrile seizures in children. The main provoking factors for the development of febrile seizures are acute respiratory viral infection, pneumonia and acute intestinal infection, and concomitant diseases (rickets of the II degree, allergic diseases, helminth invasion, I degree of malnutrition, diffuse goiter of the II degree, chronic diseases of the upper respiratory tract and urinary tract systems) create favorable conditions for the development of afebrile seizures. With febrile seizures, mainly generalized tonic-clonic seizures were observed, which can serve as a criterion for the development of afebrile seizures.